Dopamine receptor DRD1 expression (mRNA, protein level) in peripheral blood lymphocytes and prognosis of antipsychotic therapy - A. M. Zabotina; A. S. Zhuravlev; M. N. Grunina; R. F. Nasyrova; E. V. Volkova; A. A. Tyurin; O. V. Limankin; A. P. Otmakhov; E. M. Krupitsky; N. G. Neznanov; A. E. Taraskina (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2022)
Introduction. There is a problem in predicting the efficacy and safety of antipsychotic therapy. Dopamine receptor D1 is one of the targets of antipsychotics. Peripheral blood lymphocytes (PBL) are the research object of neurotransmission receptors.The objective was to study DRD1 gene expression (mRNA, protein level) in PBL as a possible biomarker of olanzapine and haloperidol therapy prognosis.Methods and Materials. Sample: 106 patients diagnosed with schizophrenic spectrum disorder. Study design: prospective longitudinal follow-up with drug administration by randomization. Assessment of mental status and development of Parkinsonism: Positive and Negative Syndrome Scale (PANSS) and Simpson-Agnus Scale (SAS), respectively. PBL was study material. DRD1 mRNA level was determined by real-time PCR. DRD1 protein concentration in PBL was measured by enzyme immunoassay.Results. Haloperidol (but not olanzapine) treatment for 28 days, leads to DRD1 protein concentration decrease in PBL in a manner dependent on its initial level. DRD1 mRNA level in PBL remained unchanged during the treatment. Patients with effective therapy by olanzapine had lower DRD1 mRNA levels. Side effects of the therapy (Parkinsonism, weight gain) were not associated with studied DRD1 parameters.Conclusions. Haloperidol treatment leads to a decrease of DRD1 protein concentration in PBL, which depends on the initial protein level. Effective olanzapine therapy is associated with reduced DRD1 mRNA level in PBL before the treatment.